2020
DOI: 10.1177/1932296820974654
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Three-Dimensional Wound Camera and Correlation With Routine Ruler Measurement in Diabetes-Related Foot Ulceration

Abstract: Background: In an era of increasing technology and telehealth utilization, three-dimensional (3D) wound cameras promise reliable, rapid, and touch-free ulceration measurements. However, reliability data for commercially available devices in the diabetes foot service setting is lacking. We aimed to evaluate the reliability of diabetes-related foot ulceration measurement using a 3D wound camera in comparison to the routinely used ruler and probe. Method: Participants were prospectively recruited from a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Studies assessing healing reported that: surface area change per day was superior to wound edge linear advancement 17 ; changes in ulcer area measured by thermal imaging correlated with healing by 12 weeks 18 ; and ulcer surface area, planimetry area and planar volume and curved volume were useful prognostic markers 19 20 . There was also good agreement between: a digital program and clinicians 21 ; 3-D cameras 22,23 ; and reproducibility of gait and plantar pressures 24 . However, inconsistent agreement between visual and objective periwound assessment was determined 25 .…”
Section: Australian Studiesmentioning
confidence: 67%
“…Studies assessing healing reported that: surface area change per day was superior to wound edge linear advancement 17 ; changes in ulcer area measured by thermal imaging correlated with healing by 12 weeks 18 ; and ulcer surface area, planimetry area and planar volume and curved volume were useful prognostic markers 19 20 . There was also good agreement between: a digital program and clinicians 21 ; 3-D cameras 22,23 ; and reproducibility of gait and plantar pressures 24 . However, inconsistent agreement between visual and objective periwound assessment was determined 25 .…”
Section: Australian Studiesmentioning
confidence: 67%
“…A total of 2610 literatures were retrieved from the preliminary search. After step‐by‐step screening, 14 literatures 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 met the inclusion criteria. The literature screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Using the ruler and probe, measurements of length (maximum diameter), width (perpendicular diameter), and maximum depth were obtained. Based on these measurements, surface area was calculated using the elliptical wound measurement method 1 and compared against the ARANZ SilhouetteStar values.…”
Section: Letter To the Editormentioning
confidence: 99%
“…In clinical settings, diabetes-related foot ulcers (DFUs) have traditionally been measured using the ruler and probe 1 ; however, this method has poor inter- and intra-rater reliability between clinicians. 2 We aimed to evaluate the reliability of the ARANZ SilhouetteStar device (ARANZMedical Ltd, Merivale, Christchurch, New Zealand) in comparison to the traditional ruler and probe method in patients with DFU in a real-world clinical setting.…”
mentioning
confidence: 99%